Structural N- and O-glycans revealed by high-resolution cryo-EM analysis of tubular mastigonemes - Junhao Huang; Hui Tao; Sheng Chen; Yahua Cui; Yiran Xu; Chuangye Yan; Nieng Yan (Science, 2026)
The chemical complexity and nontemplated biosynthesis of glycans have posed considerable challenges for establishing sequence-structure relationships. Here we report cryo–electron microscopy structures of tubular mastigonemes from a golden alga species, Ochromonas danica , in which a large number of N- and O-glycans are resolved at 1.8- to 2.2-angstrom resolution. Beyond high-mannose and complex N-glycans, we identify a noncanonical N-glycan on the Ala-Asn-Asp (AND) motif. The surface spikes comprise dense O-glycans coating PSXX tetrapeptide repeats, with two glycans linked on trihydroxylated proline and one on serine per repeat. In addition to various types of sugars and their covalent modifiers, water molecules (>10% of resolved volume) and cations are clearly resolved and mediate the structural assembly. Our study establishes a framework for investigating glycan folding in high-order biological assemblies.